Analisis Prosedur Pergerakan Helikopter dalam Pelayanan Lalu Lintas Penerbangan Perum LPPNPI Cabang Banda Aceh - Siregar, Gusnia Khairunnisa; Rosmayanti, Lina (Politeknik Penerbangan Indonesia Curug, 2024)
This study is aimed at providing advice for Perum LPPNPI Branch Banda Aceh to regulate helicopter traffic more efficiently. By using the observation method for approximately three months in Perum LPPNPI Branch Banda Aceh, there were several cases that could support the advice in order to increase the efficiency of helicopter traffic. Based on the cases, the solution for the issue concerned is by providing entry point that can act as reporting point for helicopters in the airspace of Aceh.